Daya antibakteri penambahan Propolis pada zinc oxide eugenol dan zinc oxide terhadap kuman campur gigi molar sulung non vital (The antibacterial effect of propolis additional to zinc oxide eugenol and zinc oxide on polybacteria of necrotic primary molar) - Yemy Ameliana; Herawati Herawati; Seno Pradopo (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Materials commonly used for root canal filling of primary teeth is zinc oxide eugenol. Eugenol has some disadvantages that can irritate the periapical tissues, has the risk of disturbing the growth and development of permanent tooth buds, and has a narrow antibacterial spectrum. Studies showed that propolis at concentration of 20 % has antibacterial activity against Staphylococcus aureus. Purpose: The purpose of this study was to examine the antimicrobial activity of root canal pastes with the additional of propolis additional to zinc oxide eugenol (ZOEP) and to zinc oxide (ZOP). Methods: Polybacteria cultures collected from root canals of necrotic primary molar from 5 children patients who received root canal treatment. The bacteria were grown in BHI Broth, and inoculated into Muller Hinton Agar media. The agar plates was divided into 3 areas, and one well was made at each area. The first well filled with ZOE as a control, second well filled with ZOEP and the third well filled with ZOP, then incubated for 24 hour at 370 C. Antimicrobial activity was determined by measuring the diameters of inhibition zones of polybacteria growth. The data were statistically analyzed by independent T-test. Results: The pasta mixture of zinc oxide propolis had the strongest antibacterial activity against polybacteria of necrotic primary molar, followed by zinc oxide eugenol propolis paste, and zinc oxide eugenol paste. There were significant differences of inhibition zones between ZOE, ZOEP and ZOP (p<0,05). Conclusion: The study suggested that the additional of propolis to zinc oxide paste could increase the antimicrobial effect against root canal polybacteria of necrotic primary molar.Latar belakang: Bahan yang sering digunakan untuk pengisian saluran akar gigi sulung adalah zinc oxide eugenol. Eugenol memiliki beberapa kekurangan yaitu dapat mengiritasi jaringan periapikal, beresiko mengganggu pertumbuhan dan perkembangan benih gigi permanen pengganti, serta memiliki spektrum antibakteri yang sempit. Penelitian menunjukkan propolis dengan konsentrasi 20% memiliki daya antibakteri terhadap bakteri staphylococcus aureus Tujuan: Penelitian ini bertujuan meneliti efek aktivitas antimikroba pasta saluran akar dengan penambahan propolis pada zinc oxide eugenol (ZOEP) dan pada zinc oxide (ZOP) Metode: Kultur bakteri campur diperoleh dari saluran akar gigi molar sulung 5 pasien anak yang sedang dirawat saluran akar. Bakteri ditumbuhkan dalam BHI Broth dan diinokulasi ke Muller Hinton Agar media. Plate agar dibagi menjadi 3 bagian, dan setiap bagian dibuat satu sumuran. Sumuran pertama diisi dengan ZOE sebagai kontrol, sumuran kedua diisi dengan ZOEP dan sumuran ketiga diisi dengan ZOP, kemudian diinkubasi selama 24 jam, pada 37°C. Daya antimikroba ditentukan dengan mengukur diameter zona hambatan pertumbuhan bakteri campur. Data dianalisis statistik dengan t-test independent. Hasil: Pasta campuran zinc oxide propolis memiliki daya antibakteri terhadap kuman campur gigi molar sulung non vital paling kuat, diikuti pasta zinc oxide eugenol propolis, dan pasta zinc oxide eugenol. Terdapat perbedaan zona hambat yang signifikan diantara ZOE, ZOEP dan ZOP (p<0.05). Simpulan: Penelitian ini menunjukkan bahwa tambahan propolis pada pasta zinc oxide dapat meningkatkan efek antimikroba terhadap polybacteria saluran akar dari molar sulung yang nekrotik.